2014
DOI: 10.1111/jwas.12154
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Dietary Fish Meal with Poultry By‐product Meal and Soybean Meal for Golden Pompano, Trachinotus ovatus, Reared in Net Pens

Abstract: Two 8‐wk feeding trials were conducted to examine the effect of replacing dietary fish meal with poultry by‐product meal (PBM) and soybean meal (SBM) on growth, feed utilization, body composition, and wastes output of juvenile golden pompano, Trachinotus ovatus (initial body weight 16.7 g), reared in net pens. A control diet (C) was formulated to contain 35% fish meal. In Trial I, dietary fish meal level was reduced to 21, 14, 7, and 0% by replacing 40, 60, 80, and 100% of the fish meal in diet C with PBM. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 32 publications
(77 reference statements)
2
44
2
3
Order By: Relevance
“…The FI was more in fish fed diet C than in fish fed diet R0. This result is inconsistent with the conclusion that replacing fish meal with soybean meal affects diet palatability and fish growth (Wang et al 2006;Ma et al 2014). Mani and Chandra (2003) reported that gamma irradiation on soybean cannot significantly affect FI of barbari kids, but improve FCR and nitrogen utilization efficiency.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The FI was more in fish fed diet C than in fish fed diet R0. This result is inconsistent with the conclusion that replacing fish meal with soybean meal affects diet palatability and fish growth (Wang et al 2006;Ma et al 2014). Mani and Chandra (2003) reported that gamma irradiation on soybean cannot significantly affect FI of barbari kids, but improve FCR and nitrogen utilization efficiency.…”
Section: Discussionmentioning
confidence: 78%
“…; Ma et al . ). Mani and Chandra () reported that gamma irradiation on soybean cannot significantly affect FI of barbari kids, but improve FCR and nitrogen utilization efficiency.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Golden pompano Trachinotus ovatus is widely cultured along the coast of the South China Sea (Wang, Han, Wang & Ma ). This fish requires more than 210 g kg −1 dietary fish meal when PBM, SBM or soy protein concentrate are used alone as a fish meal subsitute (Ma, Wang, Han, Wang & Lin ; Wu, Han, Qin & Wang ). Recently, the requirment of selenium (Se) in fish nutrtion has been recognized, as Se is an essential constituent of various enzymes with important physiological functions (Yoshida, Haratake, Fuchigami & Nakayama ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has indeed focused substantially on developing solutions to reduce or eliminate the adverse environmental impacts of aquaculture, and recently published articles in JWAS are noteworthy examples. For example, work continues on identifying appropriate substitutes for the use of fish meal in diets for a wide variety of aquaculture species (recent examples in JWAS include: Abdul‐Halim et al ; Ma et al ; Moxley et al ; Rossi and Davis ; Kokou et al ; Sealey et al ; Jung et al ; Song et al ). Nutritional research has begun to advance knowledge on the application of prebiotics and probiotics to improve health via the microbiome communities in the gastrointestinal tract of farmed fish and that may lead to elimination of subtherapeutic levels of antibiotic and chemical treatments to control disease (in JWAS , see Mohapatra et al ; Xu et al ; and Peredo et al ).…”
mentioning
confidence: 99%